A finite element model updating method based on global optimization. (1st May 2021) - Girardi, Maria; Padovani, Cristina; Pellegrini, Daniele; Robol, Leonardo
Highlights: The FE model updating algorithm proposed allows determining a global minimum point. The reliability and sensitivity of the parameters obtained can be estimated. Two artificial examples show the robustness and efficiency of the algorithm proposed. The method is validated via a genetic algorithm and a tool for sensitivity analysis. The material mechanical characteristic of a historical case study are estimated. Abstract: Finite element model updating of a structure made of linear elastic materials is based on the solution of a minimization problem. The goal is to find some unknown parameters of the finite element model (elastic moduli, mass densities, constraints and boundary conditions) that minimize an objective function which evaluates the discrepancy between experimental and numerical dynamic properties. The objective function depends nonlinearly on the parameters and may have multiple local minimum points. This paper presents a numerical method able to find a global minimum point and assess its reliability. The numerical method has been tested on two simulated examples – a masonry tower and a domed temple – and validated via a generic genetic algorithm and a global sensitivity analysis tool. A real case study monitored under operational conditions has also been addressed, and the structure's experimental modal properties have been used in the model updating procedure to estimate the mechanical properties of its constituent materials.